2014
DOI: 10.1007/s12028-014-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography Defines Late Hypercoagulability After TBI: A Pilot Study

Abstract: The data suggest a progressive and delayed hypercoagulable state observed days after initial TBI. The hypercoagulable state may reflect excess platelet activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Two studies also found that platelets became hyperactive following their initial dysfunction [29,37]. This was supported by a TEG study that noted increasing maximum amplitude (MA) levels 7 days after TBI [57] (MA represents clot strength that is mainly dependent on platelet function). Platelet hyperactivity could explain the increased risk of thrombosis seen in TBI patients [10][11][12][13][14][15][16][17][18]58], but future studies are warranted to assess its clinical significance.…”
Section: Primary Hemostasismentioning
confidence: 82%
“…Two studies also found that platelets became hyperactive following their initial dysfunction [29,37]. This was supported by a TEG study that noted increasing maximum amplitude (MA) levels 7 days after TBI [57] (MA represents clot strength that is mainly dependent on platelet function). Platelet hyperactivity could explain the increased risk of thrombosis seen in TBI patients [10][11][12][13][14][15][16][17][18]58], but future studies are warranted to assess its clinical significance.…”
Section: Primary Hemostasismentioning
confidence: 82%
“…2 We similarly found no difference in our results after excluding all patients with dissections. Hypercoagulability occurs during post-TBI hospitalization and leads to a 3-to 4-fold increase in VTE regardless of the presence or timing of anticoagulation 31,32 ; nonetheless, the duration of the hypercoagulability and relationship to arterial clot and ischemic stroke remain unknown. As with ischemic stroke, we found no significant relationship between tSAH and VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used TEG to identify an early hypo-coagulable state after TBI [18,19]. Massaro et al, identified and reported high MA values compared to control at 24 h after TBI (GCS \ 12) [20]. TEG has also been suggested as a screening and monitoring device for deep venous thrombosis and pulmonary embolism following brain injury [21].…”
Section: Discussionmentioning
confidence: 99%